ANALISIS TINGKAT KESEHATAN PT. BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN, TBK DENGAN METODE RISK BASED BANK RATING (RBBR) - Angel Shevania Ambarita (2023)
Banks are required to maintain a certain level of health in accordance with the provisions stated in Financial Services Authority Regulation No. 4/POJK.03/2016. The purpose of this final project is to assess the health level of PT. Bank Pembangunan Daerah Jawa Barat and Banten, Tbk using the Risk Based Bank Rating (RBBR) method. The Risk Based Bank Rating (RBBR) method is used to assess the health level of a bank, considering aspects such as Risk Profile (including Non-Performing Loan and Loan to Deposit Ratio), Good Corporate Governance (GCG) in implementing corporate governance, Earnings (Profitability) measured by the Return On Asset (ROA) ratio, and Capital (Capital Adequacy) measured by the Capital Adequacy Ratio (CAR) ratio. The analysis results of the health level assessment of PT. Bank Pembangunan Daerah Jawa Barat and Banten, Tbk indicate that the health level from 2018 to 2022 is in line with the assessment set by the Financial Services Authority, and overall, it is classified as "Healthy".